Tinjauan Perencanaan Spillway Bendungan Karalloe di Kabupaten Gowa - Nataniel Yunus Alik; Benyamin Tanan; Melly Lukman (Program Studi Teknik Sipil UKI Paulus-Makassar, 2020)
This study discusses the review of Spillway planning in the Karalloe Dam project. The spillway serves to drain excess water from the dam to avoid overtopping the dam back to the river. Three methods are used in the calculation of rainfall analysis, namely the Gumbel Method, Pearson Log Type III, and Normal Log. Design flood discharge was analyzed using the Gama-I Synthesis Unit Hydrograph Method. Spillway planning is planned based on differences in design flood discharge and Spillway lighthouse type. The results of this study obtained a design flood discharge of 613,251 m3 / sec and high energy above the lighthouse of 2,902 m using the type of round lighthouse.